Why can't we have both? A discussion on work-life balance and women career advancement in Malaysia - Mustapa N.S.; Noor K.M.; Abdul Mutalib M. (Korea Distribution Science Association (KODISA), 2024)
While the number of women labor force in Malaysia is increasing, only a few of them make it to the top. For many reasons, some women turn down top position offer and some of them refuse to stay working. Commitment to the family, work-life conflict and lack of support from the family and the colleagues are among issues that caused women to have less interest to pursue career advancement. This article examines the role of work-life balance and its relationship to women career advancement, and why both are important in Malaysia. The arguments are arranged based on a review of the previous literature to conceptualize the relationship between work-life balance and career advancement. It is found that both work-life balance and women career advancement are important to retain women in the working world as well as to motivate them to pursue promotion to a higher position. Even though some researchers agreed that the relationship between work-life balance and career advancement is mostly negative, others found positive relationship between both constructs. At the end of the paper, some suggestions on how to improve work-life balance and career advancement are presented as well as suggestion for future research.